Incidence and Long-Term Survival of Spontaneous Intracerebral Hemorrhage Over Time: A Systematic Review and Meta-Analysis - Li, Xianqi; Zhang, Li; Wolfe, Charles D. A.; Wang, Yanzhong (Frontiers in Neurology, 2022)
Background and Purpose Recent epidemiological data indicate that the absolute number of hemorrhagic stroke cases increased by 47% between 1990 and 2010 and continued to cause high rates of death and disability. The last systematic review and meta-analysis of incidence and long-term survival of intracerebral hemorrhage (ICH) were published 11 and 7 years ago, respectively, and lacked comparison between different income groups, therefore, a more up to date analysis is needed. We aim to investigate the ICH incidence and long-term survival data in countries of different income groups. Materials Methods We systematically searched Ovid Medline for population-based longitudinal studies of first-ever spontaneous ICH published from January 2000 to December 2020. We performed meta-analyses on the incidence and survival rate in countries of 4 different income groups with random-effects models (severe inconsistency). The I2 was used to measure the heterogeneity. Heterogeneity was further investigated by conducting the meta-regression on the study mid-year. Time trends of the survival rate were assessed by weighted linear regression. Results We identified 84 eligible papers, including 68 publications reporting incidence and 24 publications on the survival rate. The pooled incidence of ICH per 100,000 per person-years was 26.47 (95% CI: 21.84–32.07) worldwide, 25.9 (95% CI: 22.63–29.63) in high-income countries (HIC), 28.45 (95% CI: 15.90–50.88) in upper-middle-income countries, and 31.73 (95% CI: 18.41–54.7) in lower-middle-income countries. The 1-year pooled survival rate was from 50% (95% CI: 47–54%; n = 4,380) worldwide to 50% (95% CI: 47–54%) in HIC, and 46% (95% CI: 38–55%) in upper-middle income countries. The 5-year pooled survival rate was 41% (95% CI: 35–48%; n = 864) worldwide, 41% (95% CI: 32–50%) in high-income and upper-middle countries. No publications were found reporting the long-term survival in lower-middle-income and low-income countries. No time trends in incidence or survival were found by meta-regression. Conclusion The pooled ICH incidence was highest in lower-middle-income countries. About half of ICH patients survived 1 year, and about two-fifths survived 5 years. Reliable population-based studies estimating the ICH incidence and long-term survival in low-income and low-middle-income countries are needed to help prevention of ICH. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=170140, PROSPERO CRD42020170140.